Maghza The Story of Prophet Yusuf in the Modern Context: A Critical Discourse Study of Ustaz Firanda's Interpretation on YouTube - Aljabbar, Muhammad Muslich; Shofia, Zahrotufarhana (Civilization Research: Journal of Islamic Studies, 2025)
The story of the Prophet Joseph is one of the most prominent narratives in the Qur'an and has the title ahsan al-qasas because it contains a life journey full of trials, emotions, and exemplary. This research is important because it analyzes how social media-based da'wah is able to represent Qur'anic values relevant to modern life. This study aims to examine Ustaz Firanda's interpretation of the maghza of the Prophet Joseph's story, as well as analyze the structure and discourse strategies he uses. The research method used is qualitative with the maghza approach and Norman Fairclough's critical discourse analysis. The results showed that Ustaz Firanda highlighted moral values including patience in facing trials, guarding oneself from the temptation of women, not showing off favors, doing ihsan, and using tawriyah to avoid false speech. From the discourse aspect, this story is presented representatively as a reflection of contemporary life, building a communicative relationship with the audience through light language and contextual analogies, and creating an identity as an academic preacher. The YouTube dissemination strategy makes this lecture flexible and accessible. Socio-culturally, this lecture serves as a space for the formation of religious awareness and moral reflection that is relevant to the challenges of the times, and answers the needs of the people for digital da'wah.